For home and country World War I propaganda on the home front - Kingsbury, Celia Malone (Studies in war, society, and the military, 2010)
This work examines the propaganda that targeted noncombatants on the home front in the United States and Europe during World War I. Cookbooks, popular magazines, romance novels, and government food agencies targeted women in their homes, especially their kitchens, pressuring them to change their domestic habits.